Pseudodiverticular Colon Disease: A Therapeutic Challenge - Adolfo, García Sánchez Morelos; Mireya, De La Fuente González; Gema, Méndez Barrón; Isabel, Estrada Rodríguez María; Israel, Flores Pazos Mauricio; Astrid, Ortiz Vargas; Yamileth, Jiménez Bonola; Giselle, Castillo García; Beatriz, Li Gómez Huiyu; Sofia, Hernández Medina Myrna; Jessica, Beltrán Navarrete; Sergio, Fernández Zenteno; et al. (British Journal of Healthcare and Medical Research, 2023)
Introduction: Pseudodiverticular disease of the colon is an entity of great relevance among surgical pathologies, since it presents with a high incidence of morbidity, with diagnostic and therapeutic complexity. Their etiopathogenesis is unknown to date; it is believed that they are formed acquired by an increase in pressure within the large intestine. Aim: Present the experience of 10 years in diagnosis and treatment, in a study of four hospital centers in Mexico City. Method: It is a study with a retrospective, longitudinal, observational and descriptive design. In the Colon and Rectal Surgery services, as well as second and third level General Surgery. Results: They were classified into three groups according to incidence/presentation, with a total of 219 records, where there were a total of 123 patients with acute complicated pseudodiverticular disease, 25 cases with chronic presentation were studied, and recurrent lower gastrointestinal bleeding where 71 subjects were reported. Discussion: Treatment in acute and/or chronic complicated pseudodiverticular disease, management is surgical with no option to make a mistake, since morbidity and mortality increase exponentially with the delay of definitively decisive surgical therapy. Additionally, elective surgery reduces, but does not eliminate, the risk of recurrent diverticulitis. Conclusions: Pseudodiverticular disease is a sequela of a commonly undiagnosed underlying disease. The surgical procedure today is the Hartmann technique or two-stage surgery, which statistically presents the least morbidity and almost no mortality.